Examining Drivers of Digital Insurance Adoption in the Face of Industry Disruption: Evidence from Thai Insurance Customers - Kumpee Thamtarana; Puris Sornsaruht (My University, 2024)
This empirical research delves into customer perceptions influencing Thai insurance agencies' adoption of digital technologies.Survey data from 440 policyholders revealed that service quality, value perception, and organizational image positively shape intentions to use digital platforms, explaining a substantial 88% of variance.However, value perception's role proved minimal.Findings theoretically enrich and provide practical guidance surrounding channel migrations to online policy sales and service.The study's findings highlight the importance of DIT innovation in customer insurance sales.Manifest variables analysis indicates specific strengths within SQ, OI, VP, and DIT dimensions.The study concludes that DIT has ushered in transformative changes, creating new customer requirements and altering information search and purchasing patterns in the insurance sector.In conclusion, this research contributes actionable intelligence for policymakers and industry stakeholders in navigating the digital transition of Thailand's insurance sector.Elevating service quality and communicating innovative organizational images emerge as promising strategies.However, recognizing theoretical and methodological limitations, further mixedmethods research is recommended to validate these findings across diverse perspectives in the industry.
Keywords: Insurance industry; Insurance and Financial Risk Management